2020
DOI: 10.3390/plants9091145
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-lysine Supplementation Mitigates Oxidative Stress in Rapeseed (Brassica napus L.) by Preventing Phytotoxicity of Chromium, When Irrigated with Tannery Wastewater

Abstract: Contamination of soil and water with metals and metalloids is one of the most serious problems worldwide due to a lack of a healthy diet and food scarcity. Moreover, the cultivation of oilseed crops such as rapeseed (Brassica napus L.) with tannery wastewater could contain a large amount of toxic heavy metals [e.g., chromium (Cr)], which ultimately reduce its yield and directly influence oilseed quality. To overcome Cr toxicity in B. napus, a pot experiment was conducted to enhance plant growth and biomass by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Our results stated that increases in the level of tannery wastewater application in soil resulted in significant accumulation of Cr contents in different parts of the plant by restricting the uptake of essential nutrients like Zn and Fe (Fig 5). High concentrations of Cr contents in different tissues of plants were also detected previously [22,62,75,76]. The main effect of high concentrations of metals on the photosynthetic pigments and gaseous exchange parameters are related to decreases in the net photosynthesis rate, reduced ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) efficiency, and the inhibition of electron transport and PSII activities [37,[77][78][79].…”
Section: Plos Onementioning
confidence: 75%
See 1 more Smart Citation
“…Our results stated that increases in the level of tannery wastewater application in soil resulted in significant accumulation of Cr contents in different parts of the plant by restricting the uptake of essential nutrients like Zn and Fe (Fig 5). High concentrations of Cr contents in different tissues of plants were also detected previously [22,62,75,76]. The main effect of high concentrations of metals on the photosynthetic pigments and gaseous exchange parameters are related to decreases in the net photosynthesis rate, reduced ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) efficiency, and the inhibition of electron transport and PSII activities [37,[77][78][79].…”
Section: Plos Onementioning
confidence: 75%
“…study revealed that morphological traits of the plant including plant growth and biomass were significantly reduced through the addition of tannery wastewater in soil (Fig 1). Cr has the ability to decline the growth attributes as previously reported in different plants including B. napus [62], Zea mays [63], Helianthus annuus [64], and Triticum aestivum [65]. Cr toxicity can cause decrease in plant growth and biomass, as toxic concentration of Cr in the soil makes the uptake essential nutrients unavailable.…”
Section: Plos Onementioning
confidence: 86%
“…The response of plants to salinity differs from the sensitivity of crops at various developmental stages (Ben Abdallah et al 2013). Under salinity stress, plant growth was decreased or inhibited because of the osmotic stress and ion-toxicity, which mainly were in consequence of Na and, or Cl accumulation (Saeidi-Sar et al 2013;Nazar et al 2020;Zaheer et al 2020). In conformity with the findings of this study, in the previous study increasing salinity levels significantly decreased the fresh and dry weight of marigold flower heads (Khalid and da Silva 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the soil solution, the osmotic effects of salts lead to complicating water absorption in the plants. In addition, salinity reduces the uptake of water, key mineral elements, photosynthesis rate and pigment synthesis, enzyme activity, and secondary metabolite accumulation (Fariduddin et al 2013;Ahanger et al 2019), as well as decreasing the ability of a plant to convert energy into biomass (Alam et al 2020;Ali et al 2020;Nazar et al 2020;Zaheer et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is characterized as any external limitation of abiotic (salinity, heat, water, etc.) or biotic (herbivore) that limits the photosynthesis rate and decreases the ability of a plant to convert energy into biomass ( Alam et al, 2020 , Ali et al, 2020 , Nazar et al, 2020 , Zaheer et al, 2020b ). World agriculture faces many problems, such as the production of 70% more food for the increasing population, and crop productivity does not increase in tandem with food demand ( Ali et al, 2021 , Parihar et al, 2015 , Saleem et al, 2020b , Zaheer et al, 2020d ).…”
Section: Introductionmentioning
confidence: 99%